2006
DOI: 10.1002/jez.a.345
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning, expression and phylogenetic analyses of parvalbumin in tilapia, Oreochromis mossambicus

Abstract: The gene expression of parvalbumin (Pvalb), a high-affinity calcium-binding protein and the major fish allergen, was significantly increased in the tilapia fry treated with methyltestosterone (MT) as examined using a subtractive hybridization assay. Using the real-time quantitative PCR, we further confirmed the increased Pvalb expression in the MT-treated tilapia fry. The 568 base pairs (bp) tilapia Pvalb (tPvalb) cDNA clone was fully sequenced and found to contain a coding region of 330 bp, which encodes a 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…9). Recently, Lee et al (2007) reported on the cloning, expression and phylogenetic analysis of parvalbumin in O. mossambicus.…”
Section: Protein Electrophoresis Of Tilapiamentioning
confidence: 99%
“…9). Recently, Lee et al (2007) reported on the cloning, expression and phylogenetic analysis of parvalbumin in O. mossambicus.…”
Section: Protein Electrophoresis Of Tilapiamentioning
confidence: 99%
“…Parvalbumin from tilapia was described by Lee et al [30]. Parvalbumin from tilapia was described by Lee et al [30].…”
Section: Introductionmentioning
confidence: 99%
“…Different isoforms of parvalbumin have been identified in several catfish species (C. gariepinus, H. longifilis, Chrysichthys auratus) [47], tilapia [76] and snappers (Lutjanus argentimaculatus, L. johnii) [55]. Recently, the expression and phylogenetics of parvalbumin in tilapia (O. mossambicus) have been studied by Lee et al [54].…”
Section: Differentiation Of Catfish Tilapia and Snapper Species By Iefmentioning
confidence: 98%
“…Information on this allergen has been recently reported for tuna [49][50][51][52][53], but knowledge of parvalbumin genes and their expression in tilapia and snapper is limited [54][55][56]. IEF of sarcoplasmic proteins has been applied to identify P. hypophthalmus, P. bocourti [57] and other catfish species [58].…”
Section: Introductionmentioning
confidence: 99%